CMET-05. EVALUATING RADIATION NECROSIS IN PATIENTS WITH INTRACRANIAL METASTASES FROM MELANOMA. (11th November 2019) - Edmonds, Victoria; Thomson, Holly; Sharma, Akanksha; Butterfield, Richard; Zhang, Nan; Sio, Terence; Vora, Sujay; Daniels, Thomas; Schild, Steven; Ashman, Jonathan; Patel, Naresh; Zimmerman, Richard; et al.
Abstract: BACKGROUND: Radiation is an integral component of the multidisciplinary treatment of patients with intracranial metastasis (ICM) from melanoma. The risk of radiation necrosis (RN) post-treatment can range from 5–25%. We retrospectively evaluated pre- and post-radiation clinical and radiographical characteristics in patients with ICM from melanoma to identify potential risk factors for RN. METHODS: After IRB approval, patients with ICM from melanoma who received radiation at our institution between 2013 and 2018 were retrospectively reviewed. We recorded demographics, intracranial metastasis (burden and location), systemic therapy, resection, stereotactic radiosurgery versus whole brain radiation, and outcomes. Brain MRI was evaluated using the Response Assessment in Neuro-Oncology criteria (RANO). RESULTS: A total of 27 patients were included in the study. RN was diagnosed in 14 patients (52%) at one month to three years following radiation. Cerebellar location (n=7) was significantly associated with RN (p=0.0058). Metastasis-associated hemorrhage was present in 7 patients, 6 of which developed RN (43% vs 8%, p=0.08). Surgical resection prior to radiation was performed in 9 patients, 7 of which developed RN (50% vs 15%, p=0.1). RN appeared to be less often diagnosed when ICM were treated with higher doses of radiation (24 Gy vs 20 Gy, p=0.07). Systemic treatment was administered prior to radiation in 25 patients and we found no relationship with systemic therapy type and RN. Presumed RN was treated in 12 of 14 patients (86%). Steroids or surgical resection were the primary treatment modalities, with laser ablation used in 1 case. Following treatment, improvement was noted in 3 patients radiographically and in 1 of these clinically. CONCLUSIONS: This series of patients with radiotherapy-treated brain metastases from melanoma reveals cerebellar involvement, hemorrhage, and prior surgical resection as potential risk factors for radiation necrosis. Neoadjuvant systemic treatment did not appear to be a risk factor in our review.